Chapter Forms of government and rhetoric: perceptions of democracy and oligarchy in Demosthenes - Gontijo Leite, Priscilla (Studi e saggi, 2022)
Demosthenes is recognized as a defender of Athenian democracy and freedom, particularly in voicing his concern about the growth of Macedonian power. While the defence of democracy is a recurring theme in his speeches, Demosthenes did not develop a theory of democracy. Rather, he tended to idealize the Athenian democratic experience. Further, in his defence of democracy and the ethos of the democratic citizen, Demosthenes references oligarchy, though again not from a theoretical perspective. The objective of this paper is to analyse Demosthenes's use of the democratic and oligarchical forms of government in his defence of Athens, with a focus on his construction of an antithesis between them and his deployment of the Athenian experiences with oligarchy in 411 and 404 BC in his oratory.